ANALYSIS OF THE RELATIONSHIP BETWEEN BIOFILM FORMATION OF STAPHYLOCOCCUS AUREUS AND ANTIBIOTIC RESISTANCE IN CLINICAL STRAINS - Erkinova , Mehrangiz; Sultonaliyeva , Madina (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This analytical article examines the relationship between biofilm formation intensity and antibiotic resistance in Staphylococcus aureus strains isolated from clinical specimens. Biofilm production was evaluated as an important virulence factor that enhances bacterial resistance to environmental conditions and antimicrobial agents. Within the scope of the study, the level of biofilm formation was determined using microbiological methods and comparatively analyzed with antibiotic susceptibility profiles. The findings demonstrated that biofilm-producing strains exhibited significantly higher rates of multidrug resistance. In addition, it was considered that the biofilm matrix may hinder antibiotic penetration and contribute to the activation of resistance-related genes. The obtained results provide a scientific basis for rational antibiotic selection and the improvement of infection control strategies in clinical practice.